Optimizations of RZ5-TiC magnesium matrix composite wear parameters using Taguchi approach. Issue 5 (26th June 2018) - Mehra, Deepak; Mahapatra, Manas Mohan; Harsha, Suraj Prakash
Abstract : Purpose: The advancement in modern manufacturing technology generated the need to develop new materials for better wear resistance. The purpose of this paper is to use the Taguchi optimization approach to examine which wear parameter significantly affects weight loss and coefficient of friction for RZ5-TiC composite. It is a simple and efficient method to find performance of wear parameter using minimum experimental runs. Design/methodology/approach: RZ5-TiC composites were prepared using RZ5 as matrix, reinforced with TiC through self-propagating high-temperature synthesis technique. In the present work, an attempt has been made to study the influence of wear parameters like applied load (AL), sliding distance (SD) and Wt.% of TiC (WTC) on responses like weight loss and coefficient of friction of RZ5/TiCp composites. The pin-on-disc apparatus used to conduct abrasive wear test. The wear process parameters are optimized for minimum wear based on L27 Taguchi orthogonal design. The Taguchi technique using design of experiments (DOE) is used to obtain the data. The ANOVA and an orthogonal array are used to examine the influence of wear parameters on responses. The purpose is to examine parametric significances which affect responses. Findings: It observed that wear parameters have the significant influence on responses of RZ5/TiCp composites. The interaction of sliding distance/Wt.% of TiC is observed and found significant influence on both responses. The optimum level of the significant wear parameters is achieved based on the maximum S/N ratio for RZ5/TiCp composites. The optimal interaction for weight loss and coefficient of friction is AL1-SD1-WTC3 and AL3-SD1-WTC3, respectively. Finally, the confirmation test is conducted and the results are obtained within the confidence interval. Originality/value: The current manuscript provides an optimization of wear parameters using Taguchi approach. The extensive experimental data are used for this purpose and effects of wear parameters on responses are analyzed from the presented results. The results obtained are useful in improving the wear resistance of the RZ5-TiC composite.